A Unique Technique to Improve the Performance of Antipodal Vivaldi Antenna for Microwave Imaging Application. Issue 1 (February 2021) - Balaji, A.; Karthi, J.; Chinnammal, V.; Malarvizhi, C.; Vanaja, S.
Abstract: A highly directional Ultra-wideband (UWB) Vivaldi antenna is offered for the study of microwave imaging utilization and radar based technique. In this paper, a novel Vivaldi antenna is designed which improve the directivity, gain and bandwidth parameters of the antenna. Initially the desired performance is achieved by making some changing in the exponential tapered structure. Again some modifications are made in the top of the patch by adding some corrugations in the flaring section, so better performance improvement is obtained in the value of directivity, low frequency of operation, bandwidth and gain. The operating frequency of the tapered Vivaldi structure is 1.45GHz in the lower cut-off frequency whereas the upper cut-off frequency is 9.8GHz. The proposed corrugated Vivaldi antenna is fabricated using FR4 substrate prototype of the modified antenna is fabricated and experimentally studied as well.